A Baronial Family in Medieval England The Clares, 1217-1314 - Altschul, Michael (Johns Hopkins University Press, 2019)
Originally published in 1965. In A Baronial Family in Medieval England: The Clares, 1217-1314, Michael Altschul studies the Clare family during the thirteenth century. The Clares spearheaded the struggle to enforce Magna Carta in the Barons' War. Historians prior to Altschul tended to neglect the Clares' history given the scattered nature of the archives documenting their time as a politically influential and powerful family. This book unfolds chronologically, outlining the Clares' rise to preeminence and describing how they administered their estates and income.